Evaluation of physical growth and sexual maturation rating of Adolescent boys - Gedam, DS; Waseem, M; Chansoria, M (Journal of Nepal Paediatric Society, 2012)
Introduction: The present study is an attempt to evaluate the incidence of malnutrition as well as obesity. We have evaluated physical growth and sexual maturity rating of 10-18 years adolescent boys–overweight Vs Normal Vs Underweight. Material and Methods: A random sample of 530 adolescent boys (one private English Medium and one Govt. Hindi Medium School) between the ages of 10-18 years during the period of August 2008 to August 2009 constituted the material for this study. Weight, Height and BMI and Sexual maturation rating (SMR) were calculated. Results: Nearly 39% of the adolescent boys studied were either underweight (31%) or overweight (8%). All overweight adolescent boys have their mean weight more as compared to WHO 50th centile. Normal weight and underweight adolescent boys have lesser mean weight as compared to WHO 50th centile. All overweight and normal weight adolescent boys have their mean height lesser as compared to WHO 50th centile. All underweight adolescent boys except for age group of 12 yr have their mean height lesser as compared to WHO 50th centile. Underweight boys achieved different stages of genital growth prior to normal weight and overweight boys but lag behind as compared to Tanner. It was obvious that underweight boys achieved different stages of pubic hair growth prior to normal weight and overweight boys. Conclusion: Present study indicates that incidence of overweight children is also increasing significantly. Adolescent psychological need should be assessed and they should be given knowledge regarding their normal sexual growth pattern to decrease their anxiety. J. Nepal Paediatr. Soc. 32(2) 2012 117-123 doi: http://dx.doi.org/10.3126/jnps.v32i2.5601